Factors Affecting Profit Growth in Sharia Life Insurance Companies - Pane, Mutiara Sawitri; Ahmadi Bi Rahmani, Nur; Syahbudi, Muhammad (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
In 2021, there will be fewer Sharia life insurance providers than there were in 2020. The goal of this research is to analyze Islamic life insurance firms in Indonesia from 2016-2021 from the perspectives of claims, investment returns, underwriting outcomes, operational expenses, and profit growth. This research employs a quantitative methodology, and the analytical technique used is board information relapse inquiry with the use of Eviews 12. Secondary data were collected from five Sharia life insurance businesses registered with the AASI between 2016 and 2021. The results showed that Sharia life insurers are significantly affected by a number of factors all at once, including claims variability, investment returns, underwriting outcomes, operational expenses, and profit growth. The claim variable has moderately significant negative repercussions, whereas the investment return variable has moderately significant positive repercussions. Then, neither the underwriting outcome variables nor the operating expenses matter much.